THE ROLE OF ENGLISH IN INDIA’S LITERARY FESTIVALS AND CULTURAL DIALOGUES - Sarkar, Himadri (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Language is one of the most important components of identity and power, which plays diverse roles, especially in postcolonial countries, because people’s language use divulges historical, cultural, and even political contexts. Indian English literature is a good example of this; writers recreate themselves and the postcolonial world through the English language, which they were oppressed with. Hence, instead of perceiving the use of English as a colonial imposition, Indian English writers have made it very vibrant and resonant for cultural representation and Indian identity construction in today’s globalised world. Indian English literature is known for using code-mixing, code-switching and incorporating the local dialects, as India is a multilingual and socially diverse nation. This way, it is possible to achieve the representation of Indian ethos in literary works and mould tradition and modernity. Salman Rushdie, Arundhati Roy, Vikram Seth, as well as Jhumpa Lahiri also use language not only as narration as a linguistic means for imparting narrative but also as a platform to create further messages concerning displacement, biculturalism, the marginalisation of the Indian society and the possible modes of fighting it, respectively. In this paper, I am going to analyse how these Indian English writers employ language to claim their ethnic alterity to the English language, as well as to resist social hierarchy systems from local and global perspectives and represent the diversification of Indian regions. This creed of cultural intertwining and the role of language as a mediator between the spiritual and the material, the people’s past and present, and regional and global tendencies become evident in the selected literary works. By making their English Ian English, Kureishi and others seek to revitalise the language in Indian writing in English, which, in response, writes back to the imperialist language and successfully makes it a democratic language of the oppressed.